2014
DOI: 10.4238/2014.july.24.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic variability in in vitro sodium azide-induced Dendrobium ‘Earsakul’ mutants

Abstract: ABSTRACT. In vitro mutagenesis of Dendrobium 'Earsakul' was carried out by incubating the protocorm-like bodies in 0-5 mM sodium azide for 1 h. Twenty-eight putative mutants were evaluated for genetic variability compared to untreated control plants using inter-simple sequence repeat (ISSR) analysis. Polymorphic fragments were produced by 9 of 12 ISSR primers. A total of 173 amplified ISSR fragments varying in size from 140 to 5000 bp were obtained, 39 of which were polymorphic (22.5%). Of the 28 putative muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…It was found that the polymorphism percentage was higher in this work (34.81%) than that in our previous work (22.54%), suggesting that the polymorphism percentage may vary according to plant population used and indicating the importance of using optimal NaN 3 concentrations for inducing mutation. In both works, ISSR 818 gave high percentages of polymorphism (69.0% in this work and 42.9% in previous work), indicating its usefulness in this orchid species (Wannajindaporn et al, 2014).…”
Section: Controlssupporting
confidence: 68%
See 4 more Smart Citations
“…It was found that the polymorphism percentage was higher in this work (34.81%) than that in our previous work (22.54%), suggesting that the polymorphism percentage may vary according to plant population used and indicating the importance of using optimal NaN 3 concentrations for inducing mutation. In both works, ISSR 818 gave high percentages of polymorphism (69.0% in this work and 42.9% in previous work), indicating its usefulness in this orchid species (Wannajindaporn et al, 2014).…”
Section: Controlssupporting
confidence: 68%
“…ISSR analysis. Twelve ISSR primers homologous to microsatellite repeats and containing additional selective anchor nucleotides that were developed from the University of British Columbia and which have been used successfully in Dendrobium (Wannajindaporn et al, 2014) were chosen for the analysis. The polymerase chain reaction (PCR) was modified from Baloch et al (2010) and Brown-Guedira et al (2000).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations